PREGNANCY OUTCOMES IN THE FIRST TRIMESTER COMPLICATED BY RETROCHORIAL HEMATOMA (International Journal of Scientific Pediatrics, 2026)
Introduction. Retrochorial hematoma (RCH) in early gestation in women can predict adverse maternal, fetal, and neonatal outcomes. The relationship between the presence of RCH, its location, size, and perinatal complications was studied. Increased RCH size is associated with an increased risk of pregnancy complications such as vaginal bleeding in the first trimester, early fetal loss, fetal growth restriction, placental abruption, and preterm labor. The aim of this study was to investigate the association between first-trimester retrochorial hematoma and gestational and perinatal complications. Patients and methods. Information on 177 patients whose pregnancies in the first trimester (
Keywords: pregnancy; sonography; retrochorial hematoma; hematoma size; perinatal outcomes